“Superfícies Arrumadas”: uma análise do trágico na obra de Lygia Fagundes Telles - Eloi, Cinthia dos Santos Sacramento (2016)
This present work represents a study of work of Lygia Fagundes Telles, with the objective of analyzing the tragic presence in her narrative. To achieve this goal were used books of short stories, novels, interviews of the authoress, academic works and books about her work among them studies: Lucas (1990), Régis (1998), Silva (2001), Rufino(2007), Lucena(2008), Machado(2009) e Gomes(2011).They are analyzed the tales “Venha ver o pôr do sol”, “Uma branca sombra pálida, “Seminário dos ratos”, “Nada de novo na frente occidental”, and the novel Ciranda de Pedra (1954),investigating the complex interpersonal relationships that the characters feed and how the tragedy unleashes in their lives. We analyzed in what way the tragic is conceived in the narratives, many times from the perspective of classical tragedy, as arising from an individual failure or as the modern conception of the tragic it is inherent in human life. To support the analyzes were used studies about the tragic of the authors Aristóteles (1966), Georg Lukács (S/D), Emil Staiger (1977), Junito Souza Brandão (1985), Rymond Williams (2002), Adilson dos Santos (2005), Friedrich Nietzsche (2007), Albin Lesky (2010) and Vernant and Vidal-Naquet (2014).